The Impact of Stress on Acne - Bhaijamal, Rizwan A; Nayak, S P Srinivas (Asian Journal of Pharmaceutical Research and Development, 2023)
Introduction: Despite general acknowledgment of a link between stress and acne, few research have been conducted to evaluate this link. The purpose of this study was to discover the link between stress and acne severity. Method: The research was carried out on adolescent students chosen from Singapore's Choa Chu Kang Secondary School. A total of 94 (59%) of the 160 students invited to participate in the study accepted (43 males and 51 women), and all participants provided parental informed agreement. Mid-year exams at schools were chosen as the stress model for the study. Singaporean children undergo an intensive school examination process. The outcome of such tests has a significant impact on children's long-term employment possibilities. The Perceived Stress Scale (PSS) was utilized in this study to assess acne severity in relation to stress using the global acne grading system (GAGS). The questionnaire also contained some confounding factors related to the severity of acne. Conclusions: According to the findings of this study, it is concluded that stress has a favorable correlation with acne severity.